Arboreal camera trapping sheds light on seed dispersal of the world's only epiphytic gymnosperm : Zamia pseudoparasitica - Monteza-Moreno, Claudio M.; Rodriguez-Castro, Lilisbeth; Castillo-Caballero, Pedro L.; Toribio, Edgar; Saltonstall, Kristin (My University, 2022)
Epiphytic lifestyles have evolved independently in ecologically, morphologically, and taxonomically diverse plant species. Although this adaptation is widespread among angiosperms, it is only known to have arisen in a single gymnosperm species, Zamia pseudoparasitica (Cycadophyta). Zamia pseudoparasitica is endemic to the mountains of Western Panama, and little is known about the ecology of this unusual cycad. Here, we provide the first report of a potential seed disperser of Z. pseudoparasitica. Between late October 2019 and March 2020, we conducted arboreal camera trapping at three sites along the Talamanca Cordillera in Western Panama, yielding an accumulated survey effort of 271 camera days. Weekly direct observations were also performed using handheld binoculars at one site. Arboreal camera trapping revealed at least seven mammal species that visit this epiphytic cycad. At all three sites, the Northern olingo (Bassaricyon gabbii) was seen visiting individuals of Z. pseudoparasitica repeatedly, both while cones were closed and after they had opened. We estimated the time-varying intensity of the visits throughout our sampling and used mixed models to compare the length of visits when cones were closed versus when they were open. Both duration and time-varying intensity of visits increased after cones had opened and we documented Northern olingo removing and carrying away seeds. We also observed predation by the yellow-eared toucanet (Selenidera spectabilis) which picked and destroyed mature Z. pseudoparasitica seeds. These results suggest that the Northern olingo could be an important seed dispersal agent for this rare epiphytic gymnosperm.
Keywords: camera trap, Epiphytism, Northern olingo, Panama, seed dispersal, Zamia; 570